Parents’ Motivation in Entering Their Children to Islamic Boarding School - Firdaus Zuhri; Muhammad Amin; Maspan Maspan (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study aims to determine parents' motivation in sending their children to Islamic boarding schools, the constraints of parents in sending their children to Islamic boarding schools, and the efforts of parents to send their children to Islamic boarding schools. This type of research is classified into field research (field research). Data collection methods used are observation, interviews, and documentation. Technical analysis of the data used is descriptive qualitative with inductive and deductive thinking methods. The findings show that parents' motivation to send their children to the Nurul Jadid Islamic boarding school is that in addition to getting general lessons, Islamic boarding schools are the leading choice in educating their students. Whether it's about religious knowledge, such as understanding the classical Islamic books, the Koran, and practical worship and calligraphy, Islamic boarding schools are also places to develop children's character to be better, ethical, and civilized. So the researchers patterned motivation into intrinsic motivation and extrinsic motivation. Parents' Obstacles in sending their children to Nurul Jadid Islamic Boarding School include children not following parental rules, economic factors, community environmental factors, and parental education factors. About the efforts made by parents in sending their children to Nurul Jadid Islamic Boarding School, namely, providing advice to children, seeking additional income, and supervising the association of children.